Doctor–Patient Communication in Primary Health Care: A Mixed-Method Study in Fiji - Chandra, Swastika (Int J Environ Res Public Health, 2021)
From a clinical perspective, effective and efficient communication is part of a strategy to ensure doctors are providing high-quality care to their patients. Despite the positive impact of effective doctor–patient communication on health outcomes, limited information is available on this in Fiji. This study was carried out to determine the current patients’ perception of doctors’ communication behaviour and identify factors affecting the doctor–patient communication in Fiji. This mixed-method study was conducted in the outpatient setting of three randomly selected health centres in the Suva Subdivision, Fiji. For the quantitative phase, systematic random sampling was used to select the 375 participants who completed the structured questionnaire; of those, 20 participants were selected for the qualitative interview. From the patients’ perception, 45.6% of them perceived doctors’ communication behaviour as good, 53.6% as fair, and 0.8% as poor communication behaviour. Qualitative findings highlight factors such as the attitude of the doctors, their approach, their interaction with the patients, and them providing an explanation as important factors during doctor–patient communication. In Fiji, the majority of patients perceived doctors’ communication behaviour as fair to good and the doctors’ skills were important for effective doctor–patient communication. This study highlighted the importance of doctor–patient communication and suggested that doctors might not be practicing patient-centred care and communication; thus, they need to upgrade their patient-centred communication skills.